Modeling extracellular matrix through histo-molecular gradient in NSCLC for clinical decisions - Baldavira, Camila Machado; Prieto, Tabatha Gutierrez; Machado-Rugolo, Juliana; de Miranda, Jurandir Tomaz; da Silveira, Lizandre Keren Ramos; Velosa, Ana Paula Pereira; Teodoro, Walcy Rosolia; Ab’Saber, Alexandre; Takagaki, Teresa; Capelozzi, Vera Luiza (Frontiers in Oncology, 2022)
Lung cancer still represents a global health problem, being the main type of tumor responsible for cancer deaths. In this context, the tumor microenvironment, and the extracellular matrix (ECM) pose as extremely relevant. Thus, this study aimed to explore the prognostic value of epithelial-to-mesenchymal transition (EMT), Wnt signaling, and ECM proteins expression in patients with non–small-cell lung carcinoma (NSCLC) with clinical stages I-IIIA. For that, we used 120 tissue sections from patients and evaluated the immunohistochemical, immunofluorescence, and transmission electron microscopy (TEM) to each of these markers. We also used in silico analysis to validate our data. We found a strong expression of E-cadherin and β-catenin, which reflects the differential ECM invasion process. Therefore, we also noticed a strong expression of chondroitin sulfate (CS) and collagens III and V. This suggests that, after EMT, the basal membrane (BM) enhanced the motility of invasive cells. EMT proteins were directly associated with WNT5A, and collagens III and V, which suggests that the WNT pathway drives them. On the other hand, heparan sulfate (HS) was associated with WNT3A and SPARC, while WNT1 was associated with CS. Interestingly, the association between WNT1 and Col IV suggested negative feedback of WNT1 along the BM. In our cohort, WNT3A, WNT5A, heparan sulfate and SPARC played an important role in the Cox regression model, influencing the overall survival (OS) of patients, be it directly or indirectly, with the SPARC expression stratifying the OS into two groups: 97 months for high expression; and 65 for low expression. In conclusion, the present study identified a set of proteins that may play a significant role in predicting the prognosis of NSCLC patients with clinical stages I-IIIA.